Transformasi Digital dalam Filantropi Islam : Optimalisasi Pengelolaan Zakat dan Wakaf Melalui Fintech Syariah - Meli Saputri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explores the digital transformation in Islamic philanthropy, particularly through the optimization of zakat and waqf management using Islamic fintech. The digital economy and fintech present significant opportunities to enhance the efficiency and transparency in collecting and distributing Islamic philanthropic funds. By leveraging modern financial technology, zakat and waqf can be managed more effectively, ensuring precise and accountable distribution. The study also emphasizes the importance of Islamic financial literacy in supporting public participation in the digital economy. The findings show that integrating fintech in zakat and waqf management not only improves transparency and efficiency but also strengthens public trust in the Islamic financial system. Therefore, this research suggests further development of Islamic fintech technologies and enhanced educational programs to support the growth of Islamic philanthropy in the digital era. The research further emphasizes the necessity for comprehensive financial education programs and easily accessible information to enhance Islamic financial literacy among the broader public. Collaborative efforts between the government, financial institutions, and educational bodies are crucial to developing and promoting fintech solutions that comply with Sharia principles. Integrating technology into Islamic philanthropy not only optimizes fund management but also contributes to broader social and economic development goals by supporting more inclusive and sustainable growth. Consequently, Islamic fintech holds immense potential to revolutionize the management of zakat and waqf, fostering a more resilient and trusted financial ecosystem within the Muslim world.